Superhydrophobic Lubrication: Gas–Liquid Bilayer Reduces the Friction Between Two Solids. Issue 5 (5th January 2022) - Nurmi, Heikki A.; Yu, Cunming; Toptunov, Dmytro; Ras, Robin H.A.; Jokinen, Ville
Abstract: Lubrication is one of the most important ways to reduce the effect of friction, which is the single largest cause for energy losses in society. Typically, friction reduction is done by lubrication with petroleum‐based oils, while technology focus is shifting toward environmentally‐friendly green lubrication. Lowest friction coefficients with water‐based lubrication have previously been achieved with smooth surfaces such as silicon carbide and silicon nitride or polyzwitterionic polymer brushes with typical coefficients of friction in the order of 0.002. Here, a novel concept for green lubrication using a bilayer of water and ambient air acting as the lubricant between a hydrophilic and superhydrophobic surface is shown. This method achieves superlubricity with friction coefficients down to 0.002 as measured with oscillating tribometer and tilting stage. In addition, possible applications for superhydrophobic lubrication such as tunable lubrication and a 2D mouse treadmill, are shown. Abstract : A novel water‐based lubrication that achieves low coefficients of friction is explored. The lubrication involves a bilayer of water and air that is sandwiched between a superhydrophobic and a hydrophilic surface.